Teacher training in Special Education during the civil-military dictatorship of Pará State - Ivanilde Apoluceno de Oliveira; Maria do Perpétuo Socorro Gomes de Souza Avelino de França (Arizona State University, 2019)
This paper aims analyze teacher training during the civil-military dictatorship in Pará State from 1970 to 1985. The focus is on the Pedagogy Course, Habilitation in Mental Disability - MD at Pará State University, the only course of this type in the northern region of Brazil. The authors ask: what was the context in which the course was created? What was the theoretical-methodological basis of this Special Education course? Who was created for? These questions steer this study, based on bibliographic and documental research, and surveys sources about educational legislation and pedagogic projects of this course. This study attempts to explain the context of the course and its effects on the politics of Special Education. Among the results, it is worth noting that the civil-military dictatorship incorporated a technical education policy focused on the labor market, which contributed to consolidating the integration policy that placed the field of Special Education within psychological and therapeutic-clinical education.